A Future History of Water - Lopes, Márcia R. (2022)
The submitted text reviews the inaugural book of the anthropologist of Costan Rican ancestry, Andrea Ballestero. It is about the work A Future History of Water, published in 2019 by Duke University Press and available in open access format.